2021
DOI: 10.1093/cei/uxab039
|View full text |Cite
|
Sign up to set email alerts
|

Does CCL19 act as a double-edged sword in cancer development?

Abstract: Cancer is considered a life-threatening disease, and several factors are involved in its development. Chemokines are small proteins that physiologically exert pivotal roles in lymphoid and non-lymphoid tissues. The imbalance or dysregulation of chemokines has contributed to the development of several diseases, especially cancer. CCL19 is one of the homeostatic chemokines that is abundantly expressed in the thymus and lymph nodes. This chemokine, which primarily regulates immune cell trafficking, is involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 100 publications
1
21
0
Order By: Relevance
“…CCL19 and CCL21 are two natural ligands of CCR7 that widely exist in lymphoid organs and immune cells [ 46 ], and have been validated to be produced in large quantities by CCR7 high-expressed OSCC cell lines PCI-4B and PCI-37B [ 39 ]. Several recent studies have pointed to a strong association between CCL19&21 and cancer progression [ 64 , 65 ]. In fact, earlier researchers have highlighted the indispensable roles CCL19 and CCL21 played in attracting TAMs.…”
Section: Discussionmentioning
confidence: 99%
“…CCL19 and CCL21 are two natural ligands of CCR7 that widely exist in lymphoid organs and immune cells [ 46 ], and have been validated to be produced in large quantities by CCR7 high-expressed OSCC cell lines PCI-4B and PCI-37B [ 39 ]. Several recent studies have pointed to a strong association between CCL19&21 and cancer progression [ 64 , 65 ]. In fact, earlier researchers have highlighted the indispensable roles CCL19 and CCL21 played in attracting TAMs.…”
Section: Discussionmentioning
confidence: 99%
“…Another study identified that CCL11 was primarily expressed by α-SMA+ fibroblasts in the tumor tissue of PC patients and was involved in an enhanced stromal reaction ( 21 ). CCL19 was proposed to be a double-edged sword in cancer ( 22 ). High expression of CCL19 was associated with a favorable prognosis in PC, which was attributed to its chemotactic role in immune cells ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Choi and his colleagues discovered that IL-35 suppresses inflammation by inducing Treg cells and suppressing Th1 and Th17 cells [ 29 34 ]. These findings support Dong and Yang's (2015) findings that IL-35 is involved in various chronic inflammatory illnesses and parasitic/bacterial infections when inhibitory cytokines are present [ 35 40 ].…”
Section: Discussionmentioning
confidence: 99%